On a form of Lyapunov exponents (II: Verification and illustration) - Dinh, Nguyen Van (Vietnam Journal of Mechanics, 2005)
The form of Lyapunov exponents proposed in the part I is verified and illustrated by examining some differential equations with well-known exact solutions.